Correction of Cassicinae Bonaparte, 1853 (Aves, Icteridae) to Cacicinae Bonaparte, 1853 - Schodde, Richard; Remsen, J.v., Jr (Zootaxa, 2016)
In our recently published revised classification of the Icteridae (Remsen et al. 2016), we used the family group name Cassicinae Bonaparte, 1853 on the assumption that its type genus was Cassicus Illiger, 1811. We have since confirmed, after kind advice from Thomas Donegan (pers. comm. 2016), that Cassicus Illiger (1811: 214) is simply an unjustified emendation of Cacicus Lacépède, 1799, made clear by Illiger (l.c.) in a footnote to his description of Cassicus. Under Articles 32.5.3.2 and 35.4.2 of the International Code of Zoological Nomenclature (ICZN 1999), a family-group name formed from an unjustified emendation of the name of its type genus is to be corrected, unless the emendation has come into use as a substitute name or through prevailing use. This is not the case here, and accordingly we correct the spelling of Cassicinae to Cacicinae. Bonaparte (1853) retains authorship; and, although not expressly mentioned before, his originally ligatured suffix -eoe for the name was automatically corrected by us (Remsen et al. l.c.) under Articles 11.7.1.3 and 32.5.3 of the Code (ICZN l.c.).